The Parent Experience of Assessment Scale (PEAS): Development and Relation to Parent Satisfaction. (October 2018) - Austin, Cynthia A.; Finn, Stephen F.; Keith, Timothy Z.; Tharinger, Deborah J.; Fernando, April D.
This study outlines the development of the Parent Experience of Assessment Scale (PEAS), which is based on principles of Therapeutic Assessment. The study includes pilot testing of a 64-item questionnaire across 134 participants, with psychometric analyses utilizing confirmatory factor analysis. The revised version consists of 24 items across five subscales with appropriate internal consistency reliability (alphas from .76 to .88). The PEAS demonstrates statistically significant relations with general parent satisfaction, with two subscales indicating significant direct effects via structural equation modeling. The PEAS has the potential utility to provide more nuanced clinical and investigative feedback regarding the parent process during child psychological assessment.